Association between serotonin denervation and resting‐state functional connectivity in mild cognitive impairment. Issue 7 (5th April 2017) - Barrett, Frederick S.; Workman, Clifford I.; Sair, Haris I.; Savonenko, Alena V.; Kraut, Michael A.; Sodums, Devin J.; Joo, Jin J.; Nassery, Najlla; Marano, Christopher M.; Munro, Cynthia A.; Brandt, Jason; Zhou, Yun; et al.
Abstract: Resting‐state functional connectivity alterations have been demonstrated in Alzheimer's disease (AD) and mild cognitive impairment (MCI) before the observation of AD neuropathology, but mechanisms driving these changes are not well understood. Serotonin neurodegeneration has been observed in MCI and AD and is associated with cognitive deficits and neuropsychiatric symptoms, but the role of the serotonin system in relation to brain network dysfunction has not been a major focus of investigation. The current study investigated the relationship between serotonin transporter availability (SERT; measured using positron emission tomography) and brain network functional connectivity (measured using resting‐state functional MRI) in 20 participants with MCI and 21 healthy controls. Two SERT regions of interest were selected for the analysis: the Dorsal Raphe Nuclei (DRN) and the precuneus which represent the cell bodies of origin and a cortical target of projections of the serotonin system, respectively. Both regions show decreased SERT in MCI compared to controls and are the site of early AD pathology. Average resting‐state functional connectivity did not differ between MCI and controls. Decreased SERT in DRN was associated with lower hippocampal resting‐state connectivity in MCI participants compared to controls. Decreased SERT in the right precuneus was also associated with lower resting‐state connectivity of the retrosplenial cortex to the dorsal lateral prefrontal cortex and higher resting‐state connectivity of the retrosplenial cortex to the posterior cingulate and in patients with MCI but not in controls. These results suggest that a serotonergic mechanism may underlie changes in brain functional connectivity in MCI. Hum Brain Mapp 38:3391–3401, 2017 . ©2017 Wiley Periodicals, Inc.